Diamond coated end mills in machining silicon carbide - Konneh, Mohamed; Iqbal, Mohammad; Faiz , Nik Mohd Azwan (Trans Tech Publications, 2012)
Silicon Carbide (SiC) is a type of ceramic that belongs to the class of hard and brittle material. Machining of ceramic materials can result in surface alterations including rough surface, cracks, subsurface damage and residual stresses. Efficient milling of high performance ceramic involves the selection of appropriate operating parameters to maximize the material removal rate (MRR) while maintaining the low surface finish and limiting surface damage. SiC being a ceramic material, its machining poses a real problem due to its low fracture toughness, making it very sensitive to crack. The paper discusses milling of silicon carbide using diamond coated end mill under different machining conditions in order to determine the surface roughness parameter, Rt after the machining processes and to establish a relationship between the machining parameters and response variables. Based on the surface roughness carried out the lowest Rt obtained is 0.46 μm.